ANALISIS TINGKAT KEPUASAN WISATAWAN DOMESTIK TERHADAP PELAYANAN CUSTOMER SERVICE OFFICER DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Ambarita, Rahel; Kusuma Negara, I Made; Suwena, I Ketut (Jurnal IPTA (Industri Perjalanan Wisata); Vol 8 No 2 (2020): Jurnal IPTA (December 2020)DO - 10.24843/IPTA.2020.v08.i02.p10, 2020)
The number of passenger complaints against facilities that have not been adequately then the CSO role is absolutely essential. This research aims to increase the tourist company shall use the services of our Customer Service Officer at Airport international lawyers I Gusti Ngurah Rai of Bali. The respondents in this research totalled 190 respondents, the selection of the sample using the method of purposive sampling, the data in this study were analyzed using the Importance Performance Analysis that help by statistikal program SPSS version 17.0 for windows. The results of this study are: 1) the level of satisfaction of tourists against the Customer Service Officer in general are at the level satisfied. 2) there are varying degrees of suitability that affect the satisfaction of tourists from each variable that is Tangible variables with percentage of 96.10%, Reliability of 97.23%, amounting to 95.90% Responsiveness, Assurance of 96.63% and Empathy of 95.93%. 3) Indicator appearance and tidiness CSO is an indicator that needs to be maintained because of its implementation were in accordance with interest. 4) Indicator responsiveness of CSO in troubleshooting is an indicator of excessive in its execution.